Complementary & alternative management of Parkinson's disease: an evidence-based review of eastern influenced practices - Bega, Danny; Zadikoff, Cindy (Journal of movement disorders, 2014)
The prevalence of Parkinson's disease (PD) appears to be lower in Asia compared to the Western world. It is unclear if this is related to the ubiquitous use of traditional medicine in Eastern healthcare, but the use of complementary and alternative medicine (CAM) modalities in countries like Korea may be as high as 76%. Among patients with PD, herbal medicines, health supplement foods, and acupuncture are interventions which are increasingly used throughout the world. Countries like Korea, China, India, and Japan have long embraced and incorporated traditional medicine into modern management of conditions such as PD, but research into various CAM modalities remains in its infancy limiting evidence-based recommendations for many treatments. We reviewed the literature on CAM treatments for PD, focusing on mind-body interventions and natural products. Based on evidence limited to randomized-controlled trials we found that mind-body interventions are generally effective forms of physical activity that are likely to foster good adherence and may reduce disability associated with PD. Based on the current data, modalities like Tai Chi and dance are safe and beneficial in PD, but better studies are needed to assess the effects of other frequently used modalities such as yoga and acupuncture. Furthermore, despite centuries of experience using medicinal herbs and plants in Eastern countries, and despite substantial preclinical data on the beneficial effects of nutritional antioxidants as neuroprotective agents in PD, there is insufficient clinical evidence that any vitamin, food additive, or supplement, can improve motor function or delay disease progression in PD.